The Connection of Greece With the Trans-European Transportation and Communication Networks - Theodoros Andrianos; Michalis Karakotsoglou; Charalampos Rizos (European Regional Science Association (ERSA), 2006)
Transportation and communication networks comprise major structure components in the development of a country. The modern economic systems together with the so-called phenomenon of globalization not only demand the construction of extended networks at the dominion of a country, but their connection with networks of other countries as well. For the successful connection of transportation and communication networks certain strategies have to be implemented. The European Union (E.U.) has been a pioneer in establishing connections between its members and other countries of the continent. Thus, Trans-European Networks (TENs) of transportation, communication and energy have been created. Greece, as a member of the European Union, participates in the promotion and construction of the abovementioned networks. Within the framework of the present paper the Trans-European transportation and communication Networks of Greek interest are presented. A description of the economical and technical characteristics of these networks is given. Moreover, an attempt is made to define their expedience and feasibility, as well as the problems arising during their construction. In addition, the effects these networks have on Greek economy and regional development are examined. Finally, an effort is made to examine how these networks contribute to the best utilization of Greece's geographical position, together with overcoming the fact that Greece has no common borders with other E.U. members.
Keywords: 330